2021
DOI: 10.1007/s41207-021-00245-8
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of autochthonous and imported malaria in Spain and their relationship with meteorological variables

Abstract: Since the early twentieth century, the intensity of malaria transmission has decreased sharply worldwide, although it is still an infectious disease with a yearly estimate of 228 million cases. The aim of this study was to expand our knowledge on the main drivers of malaria in Spain. In the case of autochthonous malaria, these drivers were linked to socioeconomic and hygienic and sanitary conditions, especially in rural areas due to their close proximity to the wetlands that provide an important habitat for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The authors addressed autochthonous and imported malaria separately, highlighting that the drivers of both types of malaria are different. In fact, later studies showed that the effect of temperature as a driver of the phenology of autochthonous malaria cannot be directly extrapolated to cases of imported malaria [17]. This study concluded that the main epidemic outbreaks of malaria in Spain during the 20th century were greatly influenced by military conflicts, population movements and the worsening of hygienic and sanitary conditions.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The authors addressed autochthonous and imported malaria separately, highlighting that the drivers of both types of malaria are different. In fact, later studies showed that the effect of temperature as a driver of the phenology of autochthonous malaria cannot be directly extrapolated to cases of imported malaria [17]. This study concluded that the main epidemic outbreaks of malaria in Spain during the 20th century were greatly influenced by military conflicts, population movements and the worsening of hygienic and sanitary conditions.…”
mentioning
confidence: 77%
“…This study concluded that the main epidemic outbreaks of malaria in Spain during the 20th century were greatly influenced by military conflicts, population movements and the worsening of hygienic and sanitary conditions. Although the meteorological variables did not play a key role in these epidemic episodes, they did contribute to the latter by creating the suitable conditions for their intensification [17]. Thus, the authors of [4] asserted that modern research on this type of infectious diseases must delve into the drivers that explain the historical distribution of the disease, with the aim of differentiating the relevance of each of them in the prevalence of malaria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a continuation of implementing integrated malaria preventive measures is key to preventing the resurgence and reintroduction of malaria transmission in Makkah. In addition, understating the impact of large epidemic processes such as COVID-19 on healthcare systems and the dynamics of other infectious diseases is essential for future health policy planning and preparedness [26]. Further research is needed to determine the extent of autochthonous and imported malaria as well as the presence/resurgence of malaria vectors in and around Makkah.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there may be little doubt concerning the need for protecting MRAs from domestic travelers. Recent travel is a conspicuous risk factor for malaria acquired internationally that may occasionally result in local outbreaks in otherwise malaria-free nations [ 24 , 25 , 26 , 27 ]. Recent studies have explored domestic travel and malaria risk among residents of MRAs or nonendemic areas with MECs.…”
Section: Discussionmentioning
confidence: 99%